Improving Quality of Information: Does Integrated Reporting matter? Evidence from Sri Lankan Listed Companies - Saman Bandara; Nayomi Wijesinghe (STIE Malangkucecwara, 2023)
This study examines the information quality of Integrated Reporting (IR) adopted companies compared to non-adopted companies. Information Quality was measured in terms of the decision usefulness approach based on fundamental Qualitative Characteristics (QCs) of financial information. Data were collected through annual reports of listed companies of 26 IR-adopters and 27 non-adopters for 2010 (pre-adoption year) and 2019 (post-adoption year). The results revealed IR-adopters have significantly improved information quality from 2010 to 2019 compared to non-adopters. Also, there is a significant positive relationship between the information quality of IR-adopters with the number of years of experience in IR. Our novel QCs-based quality measurement index provides numerical measures for evaluating information quality. The study shows that IR has achieved its overall objective of improving information quality in the Sri Lankan context. Thus, it provides moral confidence for the firms expecting to adopt IR to improve their information quality in the future.